Recurrent giant neobladder calculus extrusion after bladder exstrophy repair. Issue 2 (8th December 2022) - Guimarães, Thiago; Alves, Fátima; Pinheiro, Hugo; Campos Pinheiro, Luís
Abstract : Introduction: Patients with bladder exstrophy subjected to reconstructive surgeries are at risk of developing urinary calculus. Case presentation: We report the case of a 29‐year‐old male patient with bladder exstrophy who presented with a recurrent episode of extrusion of calculus through the neobladder and anterior abdominal wall. Calculus removal and reconstructive repair of the neobladder and abdominal wall were performed in 2010. Nine years following the procedure, the patient returned with new large neobladder calculus extrusion. Conclusion: Recurrence of large calculus should be seen as the new paradigm for the importance of close follow‐up in bladder exstrophy patients.